An analysis of family size preference and attitudes toward family planning in selected areas in the Philippines - Pacheco, Antonio Romulo 1944-
This study has been done primarily with the objectives of determining whether there has been a change in the desired family size of married women at least between the younger and the older generations; to determine the extent in which different demographic and socio-economic variables affect the desired family size; and to discover the extent of the knowledge and effectiveness of the methods of contraception which these married women know in order to achieve the precariously held family size desired.